2015
DOI: 10.5964/pch.v4i2.120
|View full text |Cite
|
Sign up to set email alerts
|

School Diagnostic: Perceptions of Educational Professionals

Abstract: Aim:The school is a privileged context to prevent certain problems that may begin during the development of young students. The main objective is to assess the perceptions of educational professionals about the school structure, functioning, and organization, as well as students' behaviors. Method:We developed an exploratory study using a questionnaire, applied to a sample of 81 educational agents, teachers and non-teachers, aged between 25 and 62 years (M = 45.8, SD = 10.6). Results: Despite the positive perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 13 publications
2
8
0
Order By: Relevance
“…Based on the perception of school personnel, the results of this study allow to conclude by an moderate level of PI and SC, as well as the existence of different BP in the school context (i.e., absenteeism, disruptive behaviors and incivilities), also found in other Portuguese studies [15,16], which could impact in students' academic achievement [12], as well their social and emotional health [21]. It has been shown that a greater PI in the education of children promotes communication with school personnel [41], allowing for mediation of students' difficulties and behavioral problems detected in schools, such as situations of violence and indiscipline [41].…”
Section: Discussionsupporting
confidence: 68%
See 4 more Smart Citations
“…Based on the perception of school personnel, the results of this study allow to conclude by an moderate level of PI and SC, as well as the existence of different BP in the school context (i.e., absenteeism, disruptive behaviors and incivilities), also found in other Portuguese studies [15,16], which could impact in students' academic achievement [12], as well their social and emotional health [21]. It has been shown that a greater PI in the education of children promotes communication with school personnel [41], allowing for mediation of students' difficulties and behavioral problems detected in schools, such as situations of violence and indiscipline [41].…”
Section: Discussionsupporting
confidence: 68%
“…In addition, the literature proved the existence of a relationship between the institutional environment, interpersonal relationships, and BP, which has not been observed in other SC dimensions, that is, safety, teaching, and learning, since they were not equally considered in the analysis of the various studies [ 10 ]. The multidimensionality of the SC is very important, as it will allow one to better assess the changes to be made in the school context [ 11 ], as well as to identify the main BP disturbing the good school functioning, able to interfere with the students’ performance [ 12 ], all decisive factors to prevent the development of a delinquent trajectory [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations